Disclosure of Social Responsibility as an Effort to Communicate the Quality of Corporate Governance in Order to Improve Financial Performance - Istikhoroh, Siti; Lasiyono, Untung; Ardhiani, Mutiara Rachma; Alam, Wira Yudha; ., Noerchoidah (Journal of Ecohumanism, 2024)
This research aims to analyze the disclosure of social responsibility as an effort to communicate the quality of corporate governance to the public to enhance financial performance. The phenomenon of information asymmetry that always exists in the publication of financial statements proves the need for companies to engage in activities that communicate the quality of management governance to the public. With good communication, public trust will be built, and financial performance will improve. An empirical study was conducted on cigarette companies listed on the Indonesia Stock Exchange from 2020 to 2022. The type of research is quantitative, with data obtained by analyzing financial ratios as reported by companies on the Indonesia Stock Exchange and analyzed using the Moderated Regression Analysis technique. The research variables consist of Return on Assets as the dependent variable, Good Corporate Governance as the independent variable, and Corporate Social Responsibility as the moderating variable. Several variables measuring Good Corporate Governance, such as Managerial Ownership, Institutional Ownership, and Independent Commissioners, were found to have a partial effect on Return on Assets, while the Board of Directors and Audit Committee did not have a partial effect on Return on Assets. The analysis results prove that Corporate Social Responsibility can enhance the role of good corporate governance in influencing financial performance. This research is beneficial both theoretically and practically. Theoretically, the research results complement the literature on the determinants of financial performance, while practically, they are useful for company leaders in determining strategies to improve financial performance.Managerial Ownership